KELAYAKAN MODUL MATERI KEANEKARAGAMAN HAYATI DARI BUAH SIBO, TEMPAJO DAN PANGKOK - Anjelia, Yeyen Tia; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of modules on biodiversity material from the morphology, nutrient content and fruit fiber of sibo (Nephelium lappaceum var. lappaceum), tempajo (Lepisanthes tetraphylla Radlk.), and pangkok (Dacryodes elmeri H.J.Lam). Sibo, tempajo, and pangkok fruits were found in Tembawang Forest, Sahan Village, Bengakayang District. The research was descriptive with purposive sampling technique. Module making was followed by validation. Validation consisted of two stages namely instrument validation and teaching materials validation. This module contained three sub-material namely the concept of gene, species, ecosystems, diversity utilization of Indonesia's biodiversity and biodiversity conservation efforts in Indonesia. This module also provided information about the morphology, nutrient content and fruit fiber of sibo, tempajo, and pangkok. The module was validated by five validators with four aspects and nineteen criteria. The results of the instrument validation showed that it was feasible and corrected to use. The scores of the validation of teaching materials was calculated using the Analysis of Lawshe Content Validity Ratio (CVR) and Content Validity Index (CVI). Content Validity Index (CVI) score was 0.99 meaning that the module was categorized as valid and was worthy of being used as teaching material on biodiversity material in high school.Â Keywords: Module, Biodiversity, Sibo, Tempajo, Pangkok